Pengaruh Struktur Aktiva, Ukuran Perusahaan, Pertumbuhan Aset, dan Profitabilitas terhadap Struktur Modal pada Perusahaan Telekomunikasi di BEI Periode 2013-2015 - Heru Sulistiono; Eva Anggra Yunita (Faculty of Economics and Business, University of Pancasakti Tegal, 2017)
The purpose of this study was to determine the effect of asset structure, company size, asset growth, and joint profitability on the capital structure of the telecommunications company on the Stock Exchange for the 2013-2015 period. This research method uses a descriptive approach using a quantitative approach. The method of data collection is done by documentation. The analytical method used is descriptive statistics, classic assumption test, multiple linear regression analysis, partial test, simultaneous test, and coefficient of determination analysis. Based on the results of the partial test, the probability of a sig value is 0.216. The sig value of 0.216> 0.05 can be interpreted that there is no significant influence between the structure of assets on the capital structure of the Telecommunications company on the IDX for the 2013-2015 period. The partial test results obtained the probability of a sig value of 0.373. The sig value of 0.373> 0.05 can be interpreted that there is no significant effect between the size of the company on the capital structure of the Telecommunications company on the IDX for the 2013-2015 period. The partial test results obtained the probability of a sig value of 0.018 because the sig value of 0.018 <0.05 can be interpreted that there is a significant effect between the growth of assets on the capital structure of the telecommunications company on the Stock Exchange in the 2013-2015 period. The partial test results obtained the probability of a sig value of 0.50 sig value 0.507> 0.05 can be interpreted that there is no significant effect between profitability on the capital structure of the Telecommunications company on the IDX for the 2013-2015 period. The results of the calculation of the significance of multiple linear regression test known the significance value of multiple regression coefficients 0.015 <0.05 means that there is an influence of asset structure, company size, asset growth, and profitability jointly on the capital structure of telecommunications companies on the Stock Exchange 2013-2015 period